The Effectiveness of Using Cyberspace in Strengthening Religious Moderation among Students at Private Islamic Religious Universities - Astuti, Efi Tri; Ihsani, Fikri Amiruddin (Asketik: Jurnal Agama dan Perubahan Sosial, 2025)
This study aims to test the effectiveness of cyberspace use in strengthening religious moderation among students. Using a quantitative approach with an experimental research design. The sample consisted of 40 students of the Muhammadiyah Institute of Islamic Studies Pacitan who were divided into experimental and control groups. Data was collected through pretest and post-test, observation, and interviews. Cyberspace used in this study includes the Zoom, Instagram, YouTube, and WhatsApp platforms, which provide interactive and flexible access to various learning materials. The results of the analysis using the N-Gain Score test and Independent Sample T-Test showed that the use of cyberspace had a significant positive impact on improving the understanding of religious moderation. The average N-Gain score in the experimental group was 57%, classified as "Quite Effective". The results of the T-test showed a T-count of 5.310 which was greater than the T-table of 2.023, indicating a significant difference between the two groups. This study confirms that cyberspace, through various technology platforms, can be an effective medium in supporting the educational process, especially in strengthening religious moderation.